Profil Pasien Kanker Kolorektal di RSUP Sanglah Tahun 2019 - Krismayanti, Ni Kadek Putri Lia; Sueta, Made Agus Dwianthara; Mahayasa, I Made; Mulyawan, I Made (Universitas Udayana, 2023)
Colorectal cancer is a malignancy which that usually arises from the gland or epithelial cells of the large intestine. Based on data from GLOBOCAN 2018, colorectal cancer is the third most deadly and fourth most commonly cancer in the world. The aim of this study is to determine the profile of colorectal cancer patients at Sanglah General Hospital in 2019. This research is a descriptive study with the cross sectional method. Samples were selected from the population based on inclusion and exclusion criteria. The subjects of this study were 38 colorectal cancer patients at Sanglah General Hospital in 2019. Data were collected from medical records and it is analyzed using SPSS version 26. The result of this study showed that the profile of colorectal cancer patients at Sanglah General Hospital in 2019 greatly varied, which most occurred in the <60 years age group and dominated by male. Based on the occupation, most categories were miscellaneous (IRT and Retired) with a very normal BMI. All patients had no previous family history of colorectal cancer. The majority of the samples had a history of fiber consumption more than twice a day. Most of them did not consume alcohol with physical activity. The most common tumor’s location was in the rectum with the most histopathological findings of adenocarcinoma. Most tumor was in stage III and combination was the most common method for the management. This finding is beneficial because it provides insight into the description of colorectal cancer patients at Sanglah General Hospital in 2019. Further analytical research is indispensable to find the correlation between various variables. Keywords : Profile, Colorectal Cancer, Sanglah General Hospital